„Hellenism and Judaism”. Tadeusz Zieliński’s (1859–1944) Reflections on the Origins of Christianity - Zawadzki, Robert K. (Collectanea Philologica, 2025)
Robert K. Zawadzki examines the representation of Hellenism and Judaism in the religious studies of Tadeusz Zieliński, one of Poland’s foremost scholars of antiquity. The relationship, contacts and dealings between the representatives of the two cultures provided Zieliński with fertile ground for articulating his ideas about the origins of Christianity. By examining these conclusions, the author of this article shows how Zieliński constructed a specific image of Judaism in line with the aims and assumptions of his own work, while at the same time creating a vision of Hellenism as the real and true source of Christianity. In this article the author also proposes that Zieliński’s work should not be viewed from the perspective of contemporary religious studies, but rather as an excellent source for the history of Polish science. After all, the book is a testament not only to the author’s views, but also to the era.